Transfer and Metabolism of Cortisol by the Isolated Perfused Human Placenta - Stirrat, Laura I. (J Clin Endocrinol Metab, 2017)
CONTEXT: Fetal overexposure to glucocorticoids in utero is associated with fetal growth restriction and is postulated to be a key mechanism linking suboptimal fetal growth with cardiovascular disease in later life. OBJECTIVE: To develop a model to predict maternal-fetal glucocorticoid transfer. We hypothesized placental 11-β-hydroxysteroid dehydrogenase-type 2 (11β-HSD2) would be the major rate-limiting step in maternal cortisol transfer to the fetus. DESIGN: We used a deuterated cortisol tracer in the ex vivo placental perfusion model, in combination with computational modeling, to investigate the role of interconversion of cortisol and its inactive metabolite cortisone on transfer of cortisol from mother to fetus. PARTICIPANTS: Term placentas were collected from five women with uncomplicated pregnancies, at elective caesarean delivery. INTERVENTION: Maternal artery of the isolated perfused placenta was perfused with D4-cortisol. MAIN OUTCOME MEASURES: D4-cortisol, D3-cortisone, and D3-cortisol were measured in maternal and fetal venous outflows. RESULTS: D4-cortisol, D3-cortisone, and D3-cortisol were detected and increased in maternal and fetal veins as the concentration of D4-cortisol perfusion increased. D3-cortisone synthesis was inhibited when 11-β-hydroxysteroid dehydrogenase (11β-HSD) activity was inhibited. At the highest inlet concentration, only 3.0% of the maternal cortisol was transferred to the fetal circulation, whereas 26.5% was metabolized and 70.5% exited via the maternal vein. Inhibiting 11β-HSD activity increased the transfer to the fetus to 7.3% of the maternal input, whereas 92.7% exited via the maternal vein. CONCLUSIONS: Our findings challenge the concept that maternal cortisol diffuses freely across the placenta and confirm that 11β-HSD2 acts as a major “barrier” to cortisol transfer to the fetus.